Optimism and consumption: Psychological costs of Malaysia-Sulu dispute - Rayenda Khresna, Brahmana; Simon, Kopong; Ritzky Karina, Brahmana (Centre of Sociological Research, 2015)
This research aims to examine the moderating effect of optimism on the relationship between psychological cost and consumption level during disputes. Psychometric-based questionnaire was developed and distributed in March 2013 to find Sabahan had severe symptoms of stress. This stress level induced the consumption level and also leisure cost in attempts to overcome the dispute. Interestingly, those Sabahans who were more inclined to optimism-might rethink their consumption/spending decision making. In other words, there is a moderating effect of optimism on the relationship between stress level and consumption during disputes.